Analisis Efisiensi Rasio Luas Dimensi Apda Separator C-3-08-A di Unit Hydrocracking Unibon Plant - Herry Setiawan; Andi Jumardi; Rohima Sera Afifah; Irma Andrianti; Dharma Arung Laby; Ummul Haq; Darmiyati, Iin (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2022)
This study aims to evaluate the performance of the C-3-08A separator used in a hydrocracking unit within an industrial processing facility, in support of increased production targets. The primary focus is to calculate and analyze the Area Ratio (Rm), which represents the ratio of the separator's length to its inlet diameter, ensuring efficiency in the fluid separation process at a flow rate of 13,435 BFPD. The method applied involves manual calculations to determine the Rm value and propose improvements to the separator design based on parameters such as length and flow rate. Analysis results show that the initial Rm value of 2.527 does not meet the standard requirement, which stipulates an Rm range between 3 and 5. Recalculation suggests that extending the separator length to 36 ft yields an Rm of 3.015, meeting the standard. Additionally, reducing the flow rate to 8,000 BFPD while maintaining a separator length of 30.183 ft and diameter of 10.045 ft produces an Rm of 3.004, also within acceptable limits. In conclusion, recalculating and adjusting the separator design parameters can enhance fluid separation efficiency and support increased production outcomes.